KUALITAS ORGANOLEPTIK DAGING BABI LANDRACE YANG DIAWETKAN DENGAN METODE PENGAWETAN TRADISIONAL (SUI WU’U) DARI NUSA TENGGARA TIMUR - NAJU F. M. D.; I. N. S. MIWADA; S. A. LINDAWATI (Majalah Ilmiah Peternakan, 2022)
This research was conducted to determine the organoleptic quality of landrace pork, which is preserved by tradi- tional sui wu’u method from East Nusa Tenggara. The research was conducted from September to October 2020 at the Laboratory of Animal Product Technology and Microbiology Faculty of Animal Science, Udayana University. The experimental design used a Completely Randomized Design (CRD) with three treatments and five replicati- ons. The three treatments were: landrace pork preserved with the addition of 0.5 kg of corn flour (P1), landrace pork which was preserved with the addition of 1 kg of corn flour (P2), landrace pork which was preserved with the addition of 1.5 kg of corn flour (P3). The variables observed by flavour, color, aroma, texture and overall accep- tance. The results of the organoleptic test were analyzed using the Kruskal Wallis test and if there was a significant difference (P<0.05) then continued with the Mann-Whitney test. The results showed that the organoleptic quality (flavour, color, aroma, texture and overall acceptance) of treatments P1, P2 and P3 were not significantly different (P>0.05). The results of the study can be concluded that, the difference in the addition of corn flour in the process of preserving pork landrace with the method of preserving sui wu’u in bamboo petung for one month gives the same influence on organoleptic quality.